Application of the Discussion Method to Improve Science Learning Outcomes in Grade IV Students of MlS Al-Khoiriyah Palembang - Arnianti, Arnianti; Indraswati, Dyah (Universitas Negeri Padang, 2023)
Most of the students learning outcomes in learning are still low. This study aims to improve student learning outcomes in science class IV MIS.AL-Khoiriyah Palembang. The research method used was classroom action research method used was classroom action research. The research procedures included: planning, implementing, reflecting. The results showed that the use of the discussion method could improve student learning in class IV MIS.Al- Khoriyah Palembang. This can be seen from the percentage student learning outcomes, cycle 1 that 64,24% and in cycle 2 the value of student learning completeness increased KKM 70 and learning be seen from the percentage student lerning outcomes, in cycle 1 that is 64,24% and in cycle 2 the value of student learning completeness increased and increased and learning completeness increased and reached KKM 70 and learning completeness increased to 85,71%.